2014
DOI: 10.1007/s00384-014-1834-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an elastic girdle on lung function, intra-abdominal pressure, and pain after midline laparotomy: a randomized controlled trial

Abstract: An individually fitted elastic girdle used after midline laparotomy was found to be safe, as this did not affect lung function, coughing, intra-abdominal pressure, or wound healing. The immediate decline in lung function after surgery is restrictive and due to anesthesia and the surgical procedure. Pain was significantly decreased in the girdle group. The study is registered at ClinicalTrials.gov, number NCT01517217.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 55 publications
1
21
0
4
Order By: Relevance
“…No negative side effects on pulmonary function have been observed when using a girdle following laparotomy . Significant pain relief was seen in a recent randomized trial.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…No negative side effects on pulmonary function have been observed when using a girdle following laparotomy . Significant pain relief was seen in a recent randomized trial.…”
Section: Resultsmentioning
confidence: 97%
“…Reasons for using a post‐operative girdle are pain relief, prevention of seroma formation and improved in‐growth of the synthetic mesh . The hypothesis that abdominal binders increase the risk for pulmonary insufficiency has been disproved, forced vital capacity and expiratory volume being independent of whether patients use a post‐operative girdle or not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The review included four RCT's [99][100][101][102] and a national survey by questionnaire on the use of abdominal binders in French surgical practice [87]. One additional recent RCT was identified [103]. The French survey reported that postoperative support of the wound with an abdominal binder is common practice after major laparotomies in many surgical departments (94 % use them in some patients).…”
Section: Subcutaneous Drains In Laparotomy Incisionsmentioning
confidence: 99%
“…Despite this, the VHPQ has been used as a preoperative questionnaire, 18 and the results indicate that it is proper to use it even in this situation. To be able to evaluate postoperative pain, the degree of preoperative pain must be known.…”
Section: Discussionmentioning
confidence: 99%